A Systematic Mapping of Hybrid Games in the Academy - Paiva, Felipe; Mendonça, Glaudiney; Viana, Windson (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais Estendidos do XXI Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2022.225932, 2022)
Hybrid games can be defined as games that combine digital and analog elements in their composition. However, hybrid games bring with them challenges from both the digital and analog domains, making their development and evaluation complex. The main objective of this paper is to rise state of the art and the practice of hybrid games in academia. A standard systematic mapping methodology using digital databases for research was applied and 31 works out of a total of 395 were accepted. Through their analysis it was possible to identify the main technologies used, the areas of greatest predominance in the use of hybrid games and the methods of most used assessment.